2001
DOI: 10.1083/jcb.200104058
|View full text |Cite
|
Sign up to set email alerts
|

HES6 acts as a transcriptional repressor in myoblasts and can induce the myogenic differentiation program

Abstract: HES6 is a novel member of the family of basic helix–loop–helix mammalian homologues of Drosophila Hairy and Enhancer of split. We have analyzed the biochemical and functional roles of HES6 in myoblasts. HES6 interacted with the corepressor transducin-like Enhancer of split 1 in yeast and mammalian cells through its WRPW COOH-terminal motif. HES6 repressed transcription from an N box–containing template and also when tethered to DNA through the GAL4 DNA binding domain. On N box–containing promoters, HES6 cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…Asynchronously growing 293A cells were transfected with a reporter vector carrying the luciferase gene under the control of the basally active thymidine kinase promoter linked to five tandem copies of the GAL4 upstream activation sequence. As described previously (10,14,17), cotransfection of this reporter plasmid with GAL4bd alone led to an ϳ2-fold activation of transcription above basal level (Fig. 9D, column 2).…”
Section: Fig 4 Phosphorylation Of the Ccn And Sp Domains Of Gro/ Tlsupporting
confidence: 75%
See 1 more Smart Citation
“…Asynchronously growing 293A cells were transfected with a reporter vector carrying the luciferase gene under the control of the basally active thymidine kinase promoter linked to five tandem copies of the GAL4 upstream activation sequence. As described previously (10,14,17), cotransfection of this reporter plasmid with GAL4bd alone led to an ϳ2-fold activation of transcription above basal level (Fig. 9D, column 2).…”
Section: Fig 4 Phosphorylation Of the Ccn And Sp Domains Of Gro/ Tlsupporting
confidence: 75%
“…In particular, Drosophila Gro is required for sex determination, segmentation, and neural development (1). Vertebrate Gro/TLE proteins contribute to the regulation of neuronal development (2), patterning of the neural tube (3,4), skeletogenesis (5,6), hematopoiesis (7)(8)(9), and myogenesis (10,11). Gro/TLE proteins have no intrinsic DNA binding activity but can be targeted to specific gene regulatory regions due to their ability to interact with a number of different DNA-binding transcription factors.…”
mentioning
confidence: 99%
“…⌬WRPW (Gratton et al, 2003), and pcTOPO-Hes6-VP16 (Gao et al, 2001) were described. A PCR-based strategy was used to generate the mutated constructs pCMV2-HA-Hes6 BAD [primers basic arm defective (BAD)-F, 5Ј-GTGGAGGAGAAGGAACGCGCACGGATCAA-3Ј, and BAD-R, 5Ј-GATCCGTGCGCGTTCCTTCTCCTCCAC-3Ј] and pCMV2-HA-Hes6 LMD [primers LNHLL-motif-defective (LMD)-F, 5Ј-CT-GAACTCGCGAACCACGCGCTAGAATCC-3Ј and LMD-R, 5Ј-GGAT-TCTAGCGCGTGGTTCGCGAGTTCAG-3Ј].…”
Section: Dna Plasmids Plasmids Pcmv2-hemagglutinin (Ha)-hes6mentioning
confidence: 99%
“…6), it is capable of promoting expression of neuronal genes in vitro, as well as expanding the myotome in Xenopus embryos (Bae et al, 2000;Koyabi-Nakagawa et al, 2000;Gao et al, 2001;Cossins et al, 2002;Gratton et al, 2003). It was further demonstrated that Hes6 antagonizes and releases the transcriptional repression of Hes1 in both the neuronal and muscle lineages to promote the expression of positively acting bHLH genes, or to promote the action of positively acting bHLH factors (Bae et al, 2000;Koyabi-Nakagawa et al, 2000;Gao et al, 2001;Cossins et al, 2002;Gratton et al, 2003). Of interest, Hes1 is expressed in the cochlear epithelium adjacent to the organ of Corti Zine et al, 2001), and the number of hair cells is increased in Hes1 knockout animals Zine et al, 2001).…”
Section: Hes6 Is Not Sufficient For Hair Cell Differentiation In Cochmentioning
confidence: 99%
“…In contrast to other known Hes genes, however, Hes6 has been shown to be expressed in both precursor and differentiated neuronal cells (Bae et al, 2000;Koyabi-Nakagawa et al, 2000;Pissarra et al, 2000;Vasiliauskas and Stern, 2000;Gratton et al, 2003;Fior and Henrique, 2005). Functional studies further demonstrated that Hes6 promotes neuronal and myogenic differentiation in vitro by antagonizing the action of Hes1 (Bae et al, 2000;Koyabi-Nakagawa et al, 2000;Gao et al, 2001;Cossins et al, 2002;Gratton et al, 2003;Fior and Henrique, 2005). Here, we isolated Hes6 from the cochlear tissue by both differential gene expression and candidate gene approaches.…”
Section: Introductionmentioning
confidence: 99%